2022
DOI: 10.1111/iwj.13887
|View full text |Cite
|
Sign up to set email alerts
|

Smoking increases the risk of postoperative wound complications: A propensity score‐matched cohort study

Abstract: Cigarette smoking is associated with surgical complications, including wound healing and surgical site infection. However, the association between smoking status and postoperative wound complications is not completely understood.Our objective was to investigate the effect of smoking on postoperative wound complications for major surgeries. Data were collected from the 2013 to 2018 participant use files of the American College of Surgeons National Surgical Quality Improvement Program database. A propensity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…There was an increase in a variety of complications such as infection, wound rupture, anastomotic leakage, wound and flap necrosis, and epidermolysis and a decrease in the tensile strength of wounds of those who had a history of smoking [16][17][18]. Inoue et al found that smoking cessation for four weeks before surgery can reduce the duration of hospital stay and the rate of suture failure [19].…”
Section: Discussionmentioning
confidence: 99%
“…There was an increase in a variety of complications such as infection, wound rupture, anastomotic leakage, wound and flap necrosis, and epidermolysis and a decrease in the tensile strength of wounds of those who had a history of smoking [16][17][18]. Inoue et al found that smoking cessation for four weeks before surgery can reduce the duration of hospital stay and the rate of suture failure [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is a potent vasoconstrictor which significantly reduces blood flow to wound beds, which increases the local risk of infection, delayed healing, wound dehiscence and tissue necrosis. [22][23][24][25][26][27] This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is a potent vasoconstrictor which significantly reduces blood flow to wound beds, which increases the local risk of infection, delayed healing, wound dehiscence, and tissue necrosis. [22][23][24][25][26][27] Carbon monoxide and hydrogen cyanide, two toxic gases absorbed by the body following exposure to cigarette smoke, have also been implicated. 28 Previous studies have shown that the successful healing of a skull base repair and prevention of postoperative CSF leak is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Three risks factors (smoking, body mass index and CCI score) have consistently been shown in the published literature to be important risk factors for SSI development 22–28. Any one of these three were used to signify a high-risk patient in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were considered to be at high-risk of developing an SSI if they were smokers,22 23 or had a body mass index >35 kg/m24 25 or a Charlson Comorbidity Index (CCI) score26–28 equal to or greater than 3 2. All other patients were considered to be low-risk.…”
Section: Methodsmentioning
confidence: 99%